Surface-Enhanced Raman Scattering Physics and Applications - Kneipp, Katrin; Moskovits, Martin; Kneipp, Harald (Topics in Applied Physics,, 2006)
Almost 30 years after the first reports on surface-enhanced Raman signals, the phenomenon of surface-enhanced Raman scattering (SERS) is now well established. Yet, explaining the enhancement of a spectroscopic signal by fouteen orders of magnitude continues to attract the attention of physicists and chemists alike. And, at the same time and rapidly growing, SERS is becoming a very useful spectroscopic tool with exciting applications in many fields. SERS gained particular interest after single-molecule Raman spectroscopy had been demonstrated. This bookl summarizes and discusses present theoretical approaches that explain the phenomenon of SERS and reports on new and exciting experiments and applications of the fascinating spectroscopic effect.